Analisis Temporal Kualitas Udara dan Variasi Suhu di Kota Palembang Berdasarkan Data IQAir - Putri, Jamiatul Khairunnisa; Diansyah, Pras; Destina, Destina; Suriani, Febri; Seftini, Rien (Universitas Muhammadiyah Kendari, 2026)
Palembang is one of Indonesia’s major cities, characterized by high levels of transportation, trade, and development activity. The intensity of these activities can affect urban environmental conditions, including air quality and fluctuations in temperature over time. This study aims to analyze the temporal changes in air quality and temperature variations in Palembang City during the period of May 1–14, 2026, and to examine the relationship between the two variables. The data used consist of the Air Quality Index (AQI) obtained from IQAir and air temperature data from BMKG. The research method employed is a descriptive quantitative approach with statistical analysis, including descriptive analysis, time series graphs, Pearson correlation, simple linear regression, and t-test. The results show that the AQI values fall within the moderate category, ranging from 52 to 88, while the air temperature ranges from 26.8°C to 29.2°C and tends to be relatively stable. The correlation analysis indicates a negative relationship between temperature and AQI with a coefficient of -0.401, meaning that an increase in temperature tends to be followed by a decrease in AQI values. However, this relationship is not statistically significant (p > 0.05). The linear regression results also show that temperature does not have a significant effect on air quality. Thus, it can be concluded that changes in air quality in Palembang City are not solely influenced by air temperature, but also by other factors such as transportation activities, vehicle emissions, and other meteorological conditions.